2020
DOI: 10.2116/analsci.20p262
|View full text |Cite
|
Sign up to set email alerts
|

A Portable Smartphone-based Platform with an Offline Image-processing Tool for the Rapid Paper-based Colorimetric Detection of Glucose in Artificial Saliva

Abstract: In this study, a microfluidic paper-based analytical device (μPAD) was integrated with a smartphone app capable of offline (without internet access) image processing and analysis for the rapid colorimetric detection of glucose. A selfinking stamp was used to form hydrophobic channels on a piece of paper-towel due to its superior water absorption efficiency. As demonstrated, the developed sensor was employed for the colorimetric detection of glucose in artificial saliva in the linear scope of 0 -1 mM with a cal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The presence of light reflecting on the liquid samples during the photography could have resulted in some discrepancies in the extracted features. Microfluidic paper-based analytical devices (μPADs) are paperbased biosensors developed for disease diagnosis and can be used in photography to improve the ease of use and performance of the model [55,56]. With a better ROI, the feature extraction values can give a more accurate result, thus training models with better recognition.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of light reflecting on the liquid samples during the photography could have resulted in some discrepancies in the extracted features. Microfluidic paper-based analytical devices (μPADs) are paperbased biosensors developed for disease diagnosis and can be used in photography to improve the ease of use and performance of the model [55,56]. With a better ROI, the feature extraction values can give a more accurate result, thus training models with better recognition.…”
Section: Resultsmentioning
confidence: 99%
“…Since the 1960s, portable electrochemical glucose meters have improved the quality of life of many people who have diabetes [173]. It has been demonstrated that regular remote reporting of results using SbSs can improve patients' outcomes [174]. Older individuals tend to use their smartphones for various social and nonsocial reasons, and contrary to adolescents, elders are not associated with problematic smartphone usage [175].…”
Section: Potential Social Impact In Diagnostics For Elderly Individualsmentioning
confidence: 99%
“…It is also the most easily available body fluid in the human body. Therefore, saliva has also become a popularly studied glucose monitoring biological liquid ( Golcez et al, 2021 ). Current salivary glucose levels have been shown to positively correlate with blood glucose levels ( Bergenstal et al, 2018 ).…”
Section: Background Knowledge For Glucose Sensorsmentioning
confidence: 99%